Trusting in indigenous institutions: exporting SMEs in Nigeria. Issue 7 (22nd July 2021) - Omeihe, Kingsley Obi; Simba, Amon; Rae, David; Gustafsson, Veronika; Khan, Mohammad Saud
Abstract : Purpose: The purpose of this article is to develop new insights into the interplay between trust, indigenous institutions and weak/dysfunctional formal institutions using the Nigerian context – a developing country in Western Africa. It advances new understanding on how Nigerian entrepreneurs trust in their indigenous institutions such as family ties, kinship, chieftaincy, religion, cooperatives and trade associations to resolve disputes arising from their exporting activities as opposed to dormant formal institutions in their country. Design/methodology/approach: This exploratory study adopts an interpretive research paradigm, and it utilises a case study strategy. Data collected through observations, archival records and qualitative conversations with 36 exporting Nigerian small and medium-sized enterprises (SMEs) is analysed by utilising a combination of within and cross-case analysis techniques. Doing so enabled an in-depth study of the methods their owner-managers use in order to take advantage of the relationships they established through their long-standing cultural institutions in the place of weak formal institutions in their country. Findings: Indigenous institutions have evolved to replace formalised institutions within the business environment in Nigeria. They have developed to become an alternative and trusted arbiter for solving SMEs' export issues because of weak/dysfunctional formal institutions in the Western African country. The owner-managers of exporting SMEs perceive formal institutions as representing a fragmented system that does not benefit their export businesses. Practical implications: The findings demonstrate that there is need for policymakers to consider the role of informal institutions in the Nigerian context. Such an approach is essential given the economic importance and increasing number of SMEs that trade and export their goods through informal structures in Nigeria. Originality/value: The study indicates that it is not just the void or absence of institutions that exist in a developing country such as Nigeria, but weak/dysfunctional formal institutions have been replaced by culturally embedded informal institutions. Thus, the study provides a new theoretical avenue depicting the concept of trusting in indigenous institutions.